Existe um catolicismo de base leiga? História do Laicato na América Latina e no Caribe (1498-1955) - Scopinho, Sávio Carlos Desan (Revista eclesiástica brasileira, 2010)
This article studies the presence of the laity in the Latin American Catholicism, from the beginning of colonization (1948) to the first half of the XX century. In this period, the Catholic Church has been structured in a hierarchic form, making the laity a “clergy auxiliary”, as stated by the First Latin American Episcopal Conference (Rio de Janeiro – 1955). Therefore, the objective of this article is to demonstrate that the laity had pseudo-autonomy in the colonial period and also, was a collaborator of hierarchy, through the General and Specialized Catholic Action, in the period of formation of the national states. This historical view helps to understand the conclusions of the Latin American Episcopal Conferences in Medellín (1968), Puebla (1979), Santo Domingo (1992) e Aparecida (2007), regarding the role of laity inside the Church and the society.